Escarificação como forma de incorporação de calcário em um latossolo vermelho sob plantio direto - Vieira, Márcio Luis (2010)
In the no-tillage(NT)where the seeding is performed in soil covered with crop residues with minimum tillage, when handled improperly, and continued, compaction can occur, with all its negative consequences on production and environmental conservation. Allied to this in those areas under tillage,lime and fertilizer are applied on the surface or incorporated by the seed drills of seeders subsurface, which causes a concentration gradient of nutrients or toxic elements in the surface layer relative to the rest of the profile. The limitations of physical and chemical soil lead concentration in depth of the root system in the surface layer, predisposing plants to water deficit. The present study aims to analyze the changes in physical and chemical properties of an Oxisol of the Passo Fundo (RS), conducted under no-tillage and subjected to different methods of decompression and correction of the soil with lime, and the effect of these changes on crop yields. The treatments were: no-tillage (NT), chiseled (C), no-tillage with lime surface (NT+LS), chiseled with lime surface (C+LS), chiseled with lime surface and embedded (C+LS+E) and chiseled with lime embedded (C+E). The following soil parameters were assessed: the texture, consistency, bulk density and particle density, the relative density, porosity, maximum density of the soil, penetration resistance (PR) and least limiting water range (LLWR), pH H2O,SMP,MOS,levels of P, K, Ca, Mg, Al, H + Al, base saturation, Al saturation, and K, CTC and micronutrients.. The crops were: oats, wheat, and barley(2006), soybean (2006-07), sunflower (2007-08)and corn (2008-09). The results indicated that groups of management with tillage showed bulk density, relative density, porosity, maximum density and PR than the NT group managements, proving to be an alternative for the conservation of soil and water, with effects that lasted for over 18 months. The LLWR had similar critical density between soil managements. From the chemical point of view, the ph H2O, SMP increased in plots that contemplated application of lime in different methodologies, reducing the levels of exchangeable aluminum, reducing the potential acidity of the soil and increasing base saturation, being restricted depth 10 cm. The yield of crops was different in the systems of soil management and crop years. It is concluded that the improvement in chemical (pH increase and reduction of acidity and aluminum saturation) and physical (reduction of bulk density and PR and increase in porosity) conditions of the soil cannot always be reflected in crop yields, and greatly influenced by prevailing climatic characteristics